Selection and genetic evaluation of pig origin of the English company «BPB «Zolotonishskyi» on their own productivity indicators - Небилиця, М. С.; Новицький, В. П.; Миронченко, В. Г. (Scientific Progress & Innovations, 2012)
It is noted that when working with animals of specialized breeds of imported origin, score on a comprehensive class, so far, is very little informative. A high correlation coefficient (r = - 0,825) between the values of evaluation indices Eve-il and Er has been set. Evaluation of rearing pigs on the basis of the index is more accurate than estimates for the independent level and rank. In particular, the result of the research found that in terms of evaluation indexes among the animals of Large White breed of English origin, boars were significantly superior to their peer sows.